UNDERSTANDING INDIVIDUAL TAXPAYER COMPLIANCE: THE ROLES OF TAX SERVICE QUALITY, TAX LITERACY, AND PAYMENT MOTIVATION - Ritz Erick Imanuel; I Gusti Ketut Agung Ulupui; Ayatulloh Michael Musyaffi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2026)
This study aims to analyze the effect of tax service quality, tax literacy, and tax payment motivation on individual taxpayer compliance in the Greater Jakarta area (Jabodetabek). The research employed a quantitative approach using a survey method by distributing questionnaires to individual taxpayers. Data analysis was conducted using Structural Equation Modelling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results indicate that tax service quality, tax literacy, and tax payment motivation have a positive effect on taxpayer compliance. Among the independent variables, tax literacy demonstrates the most dominant influence on taxpayer compliance. The outer model testing confirms that all indicators are valid and reliable, with outer loading values above 0.70, AVE values above 0.50, and composite reliability values above 0.70. The findings are expected to provide recommendations for the Directorate General of Taxes in improving taxpayer compliance through optimizing tax services, enhancing tax education, and strengthening taxpayers’ motivation to fulfill their tax obligations. These findings highlight the importance of enhancing tax service quality and strengthening motivational aspects to improve tax compliance, especially within increasingly digitalized tax administration systems.